2010
DOI: 10.5551/jat.4358
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supervised Aerobic Exercise Training on Serum Adiponectin and Parameters of Lipid and Glucose Metabolism in Subjects with Moderate Dyslipidemia

Abstract: Aim:To examine the effects of supervised aerobic exercise training on serum adiponectin and lipids, including triglyceride (TG)-rich lipoproteins, in moderate dyslipidemic subjects. Methods: Twenty-five dyslipidemic patients [mean body mass index (BMI) 24.6 kg/m 2 ; mean age 39 years; mean total cholesterol 226 mg/dL; mean TG 149 mg/dL] without metabolic syndrome, diabetes, and hypertension underwent supervised aerobic exercise training (60 min/day, 2 to 3 times/ week) at an intensity of 60 − 80% of age-predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 34 publications
(40 reference statements)
4
30
1
2
Order By: Relevance
“…We showed a significant increase of the total serum adiponectin and HMW adiponectin after 12 weeks of moderate aerobic training combined with a significant reduction of fasting blood sugar, fasting insulin, glycosylated hemoglobin, and insulin resistance, with no significant relationship between the reduction of the BMI or insulin resistance, and the increase of total serum adiponectin or HMW adiponectin. Our findings are in accordance with those of some previous studies that reported that even one week of exercise training increased adiponectin levels and insulin sensitivity in obese subjects without weight loss [19], and aerobic exercise training two to three times per week in the presence of weight loss had increased the adiponectin levels and insulin sensitivity at week 16 in obese subjects with moderate dyslipidemia [22]. By contrast, our finding are inconsistent with other studies that found that acute and chronic exercise does not affect adiponectin levels in lean and healthy subjects after 20 and 8 weeks of intensive training that reduced abdominal fat and increased insulin sensitivity, but had no effect on adiponectin in diabetic men [21].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We showed a significant increase of the total serum adiponectin and HMW adiponectin after 12 weeks of moderate aerobic training combined with a significant reduction of fasting blood sugar, fasting insulin, glycosylated hemoglobin, and insulin resistance, with no significant relationship between the reduction of the BMI or insulin resistance, and the increase of total serum adiponectin or HMW adiponectin. Our findings are in accordance with those of some previous studies that reported that even one week of exercise training increased adiponectin levels and insulin sensitivity in obese subjects without weight loss [19], and aerobic exercise training two to three times per week in the presence of weight loss had increased the adiponectin levels and insulin sensitivity at week 16 in obese subjects with moderate dyslipidemia [22]. By contrast, our finding are inconsistent with other studies that found that acute and chronic exercise does not affect adiponectin levels in lean and healthy subjects after 20 and 8 weeks of intensive training that reduced abdominal fat and increased insulin sensitivity, but had no effect on adiponectin in diabetic men [21].…”
Section: Discussionsupporting
confidence: 83%
“…This inconsistency between the results of this study and the previous studies may be in part related to the subjects who participated in the other studies, and whether they were diabetic or nondiabetic or to the intensity and duration of exercise training and the baseline values of insulin resistance and BMI. The increased total adiponectin and HMW adiponectin seen in this study could be interpreted by the significant reduction of body weight in the participating patients at the end of the 12 weeks of moderate aerobic training because it has been found that the adiponectin did not increased significantly after two weeks of training without reduction of body weight, but after 16 weeks of training adiponectin levels had a significantly reduced association with a significant reduction in body weight [22].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Human studies, however, show somewhat divergent results. Long-term training has shown both decreased and unchanged VLDL-TG levels (16,17), but whether the reduction (16) was due to reduced hepatic secretion or increased peripheral clearance of VLDL-TG is not clear. On the other hand, 6 months of supervised endurance training was associated with decreased apoB-100 secretion, a measure of VLDL particle number, examined by [1-13 C]leucine tracer (18).…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity is widely acknowledged to reduce the risk of cardiovascular disease in individuals with established disorders such as obesity, hypertension, DM, and hyperlipidemia [4][5][6][7][8][9]. Meanwhile, new alternatives for traditional altitude training regimes have been proposed, known as "living low and training high", and the effects on endurance performance have been demonstrated extensively in athletes [10][11][12].…”
Section: Introductionmentioning
confidence: 99%